2002
DOI: 10.1111/1475-3588.00004
|View full text |Cite
|
Sign up to set email alerts
|

The Little Hulton Project: A Pilot Child Clinical Psychology Service for Pre‐School Children and their Families

Abstract: A community-based early intervention psychology service for pre-school children with emotional and behavioural problems is described. The intervention included parent training groups, a weekly open clinic, and multi-agency training, liaison and consultancy. The aims were to provide successful intervention to families, to maximise liaison with community staff and to provide a seamless service to and from the main hospital department. Evidence indicated improvements in parental coping and children's behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Self‐referred parents were recruited through a community outreach program. The outreach program involved mental health professionals visiting preschool centers in communities with known high levels of need, and encouraging parents to join the parenting programs (for further details, see White, Agnew, & Verduyn, 2002). All parents who took part in the study were experiencing moderate or severe difficulties with their preschool child's behavior, and were living in an area that experiences a high level of social and economic deprivation (Salford & Trafford Health Authority, 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐referred parents were recruited through a community outreach program. The outreach program involved mental health professionals visiting preschool centers in communities with known high levels of need, and encouraging parents to join the parenting programs (for further details, see White, Agnew, & Verduyn, 2002). All parents who took part in the study were experiencing moderate or severe difficulties with their preschool child's behavior, and were living in an area that experiences a high level of social and economic deprivation (Salford & Trafford Health Authority, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Material covered included learning to give children positive attention through play; learning to increase good behavior by paying it increased attention by using “specific labelled praise” and frequent small rewards; learning to give commands in a manner that is most acceptable to children; learning to withdraw attention for inappropriate behavior; & learning to use “time out” for dangerous & destructive behaviors. Interested readers are referred to White, Agnew & Verduyn (2002) and White, McNally, & Cartwright‐Hatton (2003) for a more detailed description of the program. Group leaders were mental health professionals with a nursing/clinical psychology background who were blind to the hypothesis of the study.…”
Section: Methodsmentioning
confidence: 99%
“…There is good evidence for the components of an effective community service to target children and families with early emerging behaviour problems. Both clinic‐based and community randomised controlled trials have shown that improving parenting skills via parent groups are effective in changing both parents’ and children’s behaviour (Gardner, Burton, & Klimes, 2006; Hutchings & Lane, 2006; Hutchings & Gardner et al, 2007; Kazdin, 1995; Scott et al, 2001; Webster‐Stratton, Reid, & Hammond, 2001; White, Agnew, & Verduyn, 2002; White & Verduyn, 2006). In addition to parenting groups, consultative working and training with nursery staff and teachers adds to the likely success of intervention programmes (Webster‐Stratton & Reid, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to parenting groups, consultative working and training with nursery staff and teachers adds to the likely success of intervention programmes (Webster‐Stratton & Reid, 2004). Another important strand of a comprehensive community service is the need to be able to address individual parent concerns (both about their role as a parent and also their own situation) that also helps with engagement, especially of traditionally difficult‐to‐reach parents (Hutchings & Lane, 2006; Sanders & Turner, 2005; Scott, 2006; White et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article on the development of parenting initiatives, Day and Davis (1999) comment that a missing component in these approaches is the availability of social support to parents, which could be offered through a parenting group approach. White, Agnew and Verduyn (2002) describe an early intervention psychology service for preschool children with emotional and behavioural problems, which adopts this model of service delivery and provides parent training groups, open clinics and multi‐agency support and training. Those attending parent training groups, based within the community in an area of high socio‐economic deprivation in Salford, reported improvements in parental coping and children's behavioural difficulties that were maintained at 12‐month follow‐up.…”
Section: Introductionmentioning
confidence: 99%